The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1678-77572009000700015
|View full text |Cite
|
Sign up to set email alerts
|

Dental anxiety and pain related to ART

Abstract: Atraumatic Restorative Treatment (ART) is considered to be well accepted, both by children and by adult patients. The objective of this review is to present and discuss the evidence regarding the acceptability of ART, from the patient's perspective. Aspects related to dental anxiety/fear and pain/discomfort have been highlighted, to facilitate better understanding and use of the information available in the literature. Conclusions: The ART approach has been shown to cause less discomfort than other conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 19 publications
1
42
0
3
Order By: Relevance
“…The pain variable was associated with the type of treatment, irrespective of the order in which they were performed, showing that the children that received conventional treatment experienced more pain than those who received ART, which supports the findings of other papers (LEAL; ABREU; FRENCKEN, 2009;GOUD et al 2012;MOTTA et al, 2013;GEETHA PRYA et al, 2014). ART is considered to be one of the examples of the new paradigm -Minimally Invasive Dental Care -used to control decay and in the promotion of healthcare (SERPA et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The pain variable was associated with the type of treatment, irrespective of the order in which they were performed, showing that the children that received conventional treatment experienced more pain than those who received ART, which supports the findings of other papers (LEAL; ABREU; FRENCKEN, 2009;GOUD et al 2012;MOTTA et al, 2013;GEETHA PRYA et al, 2014). ART is considered to be one of the examples of the new paradigm -Minimally Invasive Dental Care -used to control decay and in the promotion of healthcare (SERPA et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…Studies indicated that the use of manual instruments without the need for anesthesia during ART would make this technique more comfortable and more acceptable in the dental environment (LEAL; ABREU; FRENCKEN, 2009;AGUILAR et al, 2012); however, despite presenting low pain levels, ART did have a longer average procedure time, resulting in the mouth being kept open for a longer period of time during the first session, probably influencing the previous anxiety levels in the subsequent session. GEETHA PRYA et al (2014) reported that the children submitted to protracted treatment during the caries removal procedure, presented scores of 3 and 4 on the FIS scale and they preferred the drill due to the shorter caries removal time.…”
Section: Discussionmentioning
confidence: 99%
“…130 Similarly, while one review of the literature on ART suggests 'that it is a suitable approach to be used in children, the elderly, special needs patients, or patients who demonstrate fear and anxiety towards dental treatment' (p. e672), 131 another review concludes that the association between different restorative procedures and dental anxiety, pain and discomfort is contradictory and requires further investigation. 132 For people who feel anxiety in relation to the noise, vibration, discomfort or pain of a standard rotary drill, air abrasion offers another worthwhile alternative. In addition, it reduces the need for anaesthesia, which is a source of concern for many anxious children and adults.…”
Section: Alternative Methods For Tooth Preparationmentioning
confidence: 99%
“…Elimination of anxiety triggers, namely, the B4S^rule (sights, sounds, sensations, and smells) [2] is important for all patients undergoing restorative dental procedures. The sight of a drill and a local anesthetic needle syringe, along with a high-pitched sound and high-frequency vibration of the dental turbine, are the significant sources for dental anxiety, which drive the expectation of dental pain [3][4][5]. Lasers have been shown to produce 400 times less vibration, than does a burr preparation [6], and achieve an improved patient experience, as evidenced by a number of pediatric studies.…”
Section: Introductionmentioning
confidence: 99%